The effect of sexual disorders on divorce and legal strategies to prevent it - Azad Sarvestani, Fateme; Mina, Mahbobe (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study is to review some of the provisions of the Family Protection Act of 2012 and civil law to prevent the collapse of the family in a case whose subject is the sexual defects. Method: The present study uses a descriptive-analytical method and has been written using judicial opinions, books, dissertations and valid articles. Results: According to the findings of this study, in order to strengthen the family’s foundation, couples’ sexual disorders must be examined before marriage registration, and the dissolution of marriage due to termination and divorce should also be required to reform their couples. Treatment. In order to protect the rights of the wife under certain circumstances, although the couple’s defect is treatable, the right to terminate the marriage for the wife remains a fault, and by providing sexual disorders in Article 6 of the Civil Code, the difficulty of proving the spouse shall be abolished. Conclusion: Sexual disorders that are treatable should not be considered as the dissolution of marriage, and the court should refer the couples to specialized centers for treatment. Reviewing some of the provisions of the Civil Code and the Family Protection Act of 2012 can cause timely diagnosis and treatment of couples’ sexual disorders and reduce the number of marriage dissolution statistics.